Intracranial hemorrhage detection over time using susceptibility-weighted magnetic resonance imaging. (December 2015) - Schelhorn, Juliane; Gramsch, Carolin; Deuschl, Cornelius; Quick, Harald H; Nensa, Felix; Moenninghoff, Christoph; Schlamann, Marc
Background: The reliable detection of intracranial hemorrhages is important, but just 1 year after the hemorrhage onset it might be missed using T2-weighted spin-echo and gradient-echo sequences. Susceptibility-weighted imaging (SWI) is a new magnetic resonance imaging sequence that is extremely sensitive in hemorrhage detection and that might improve the detection of hemorrhages over time. Purpose: To investigate whether the detectability of intracranial blood and its degradation products is independent of the time span after intracranial hemorrhage using SWI. Material and Methods: Sixty-six consecutive patients (28 men, 38 women) with definitely known time point of intracranial hemorrhage and available SWI sequence (1.5 or 3 T) were analyzed retrospectively. Twenty-one patients had a SWI follow-up. All SWI images were assessed by two radiologists in consensus regarding hemorrhage visibility using a 5-point scale. Statistical analysis was performed using Spearman's correlation test. Results: Median time interval between hemorrhage and first available SWI measurement was 819 days (range, 0 days to 13.2 years). Nine of 66 patients had an isolated subarachnoid hemorrhage (iSAH) and were therefore analyzed separately. In eight of these nine patients the hemorrhage could clearly be detected, the remaining one had minor iSAH. Spearman analysis showed no significant correlation between time span and visibility ( P  = 0.660). In the remaining 57 patients (no iSAH) the hemorrhage was always visible achieving at least 3/5 points on the 5-point scale, and Spearman's analysis revealed only a weak correlation between time span and visibility (r = 0.493, P  < 0.001). Conclusion: The detectability of blood and its degradation products using SWI is reliably possible over a long period after intracranial hemorrhage.